Therapeutic Potential of Natural Compounds to Modulate WNT/β-Catenin Signaling in Cancer: Current State of Art and Challenges - Gajos-Michniewicz, Anna; Czyz, Malgorzata (International journal of molecular sciences, 2024)
Targeted therapies and immunotherapies have improved the clinical outcome of cancer patients; however, the efficacy of treatment remains frequently limited due to low predictability of response and development of drug resistance. Therefore, novel therapeutic strategies for various cancer types are needed. Current research emphasizes the potential therapeutic value of targeting WNT/β-catenin dependent signaling that is deregulated in various cancer types. Targeting the WNT/β-catenin signaling pathway with diverse synthetic and natural agents is the subject of a number of preclinical studies and clinical trials for cancer patients. The usage of nature-derived agents is attributed to their health benefits, reduced toxicity and side effects compared to synthetic agents. The review summarizes preclinical studies and ongoing clinical trials that aim to target components of the WNT/β-catenin pathway across a diverse spectrum of cancer types, highlighting their potential to improve cancer treatment.